Synthesis of directly fused porphyrin dimers through Fe(OTf)3-mediated oxidative coupling1. Issue 9 (7th March 2015) - Feng, Chuan-Mi; Zhu, Yi-Zhou; Zhang, Shao-Chun; Zang, Yun; Zheng, Jian-Yu
<x xml:space="preserve">Abstract</x> A practical and general Fe(OTf)3-mediated oxidative coupling method was developed for the synthesis of doubly or triply linked porphyrin dimers.